Вияв категорії порівняння у структурі художнього мовлення Григора Тютюнника - Звягіна, Ганна Олександрівна (My University, 2015)
У статті досліджуються основні вияви категорії порівняння в художніх творах Григора Тютюнника, виявляються групи порівнянь за семантичними та граматичними ознаками. Порівняння в новелах та повістях Григора Тютюнника розбиваються на семантичні поля та семантичні типи, групуються за типами сполучників. Визначається призначення та синтаксичні функції порівнянь у творах Григора Тютюнника. В статье исследуються основные проявления категории сравнения в художественных произведениях Григора Тютюнника, виявляються групппы сравнений по семантическим и грамматическим признакам. Сравнения в новеллах и повестях Григора Тютюнника розбиваються на семантические поля и семантические типы, группируються по типам предлогов. Определяються назначение и синтаксические функции сравнений в произведениях Григора Тютюнника. The main use of the category of comparison in the stories of Hrigir Tiutiunnyk is explored in the article, the groups OF comparisons after semantic and grammatical signs appear. Comparisons in the stories of Hrigir Tiutiunnyk are broken up on the semantic fields and semantic types, is formed group after the types of unions. Setting of comparisons and syntax functions in the stories of Hrigir Tiutiunnyk is determined. In our research lean against determination of comparative turn is the separated part of sentence, which is used with the special semantic-syntax. The category of comparison in a simple unelementary sentence foresees four components. The category of comparison also will be realized in difficult suggestion. The permanent use of comparative turns and an unusual combination of such units are investigated. The choice of comparisons testifies in accordance with semantic types, that types prevail «man-man», «man-zoon», «manlifeless creature», «man-musical instrument», «man-plant». Among unions most common «as» (як). The row of voice selects in the analysed stories and short stories also, smell, haptic, after similarity and in size, visual comparative turns. Asyndetic comparison is a construction with lexically expressed a subject, object and basis of comparison. Absence of connecting element as a syntactic index of assimilation is compensated the specific grammatical form of object of comparison which specifies on comparative copulas within the limits of construction. A comparative turn can execute different syntactic functions: comparative determination, comparative predicate, appendixe.
Keywords: порівняння; семантичні поля; семантична структура; сравнение; семантические поля; семантическая структура; comparison; semantic fields; semantic structure